Supervisi Mutu Pembelajaran IPA Pada SDN 3 Wolowaru - Jumilah Gago (Ekspektasi: Jurnal Pendidikan Ekonomi, 2021)
The problem in this research is how to supervise the quality of science learning at SDN 3?. The purpose of this study was to determine the quality supervision of science learning at SDN 3 Wolowaru. The approach used in this study is qualitative, namely an approach that tries to understand the individual meaning of the subject under study. The subjects of this study consisted of key informants, namely the principal as a supervisor and informants, namely the science subject teacher. In obtaining the data, the writer uses interview, observation, and observation techniques. The results showed that 1. the role of the principal as a supervisor: a. the principal's duty as a supervisor is to make teachers more serious and enthusiastic and responsible in teaching and learning activities, b. the function of the principal as a supervisor is to provide direction, guidance, service and supervision. 2. The supervision process at SDN 3 Wolowaru: has been carried out well by the principal as a supervisor, starting from the supervision program, implementing supervision, as well as the follow-up process from the results of supervision. 3. The views of the science subject teachers are very helpful in improving the quality of learning as well as influencing and improving the learning process.